Guselkumab, Risankizumab, and Tildrakizumab in the Management of Psoriasis: A Review of the Real-World Evidence - Ruggiero A; Picone V; Martora F; Fabbrocini G; Megna M (Dove Medical Press, 2022)
Angelo Ruggiero, Vincenzo Picone, Fabrizio Martora, Gabriella Fabbrocini, Matteo Megna Department of Clinical Medicine and Surgery, Section of Dermatology, University of Naples Federico II, Naples, ItalyCorrespondence: Angelo Ruggiero, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Napoli, 80131, Italy, Tel +39 081 7462457, Fax +39 081 7462442, Email angeloruggiero1993@libero.itAbstract: Interleukin (IL)-23 inhibitors, guselkumab, risankizumab, and tildrakizumab, represent the latest class of biologics approved for the treatment of moderate-to-severe psoriasis. Since their approval numerous real-life studies were published on anti-IL-23 use in routine clinical practice. Indeed, real-life data are important to improve the dermatological decision-making process, including patients who are typically excluded from clinical trials, such as subjects suffering from several comorbidities, subjects on polypharmacy, as well as multifailure patients. Herein, we performed a comprehensive literature review about real-life data available on guselkumab, risankizumab, and tildrakizumab. Real-life data of anti-IL-23 seem to confirm the promising results of IL-23 shown by clinical trials, highlighting the efficacy and safety profiles of this new class of biologics also in clinical practice.Keywords: guselkumab, tildrakizumab, risankizumab, psoriasis, review, real life, real-world practice, real-world evidence